A solid electrolyte material and its preparation method and application

By using Li6+xPSe5+xI1-x solid electrolyte material in all solid state lithium batteries, adjusting the Se2-/I- ratio and using stable P-Se bonds, the problems of low conductivity and instability of sulfide electrolyte materials are solved, and efficient ion transport and battery cycle stability are achieved.

CN118507816BActive Publication Date: 2025-03-04INNOVATION ACAD FOR PRECISION MEASUREMENT SCI & TECH CAS +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410402840.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2025-03-04
Estimated Expiration
2044-04-03

AI Technical Summary

Technical Problem

In existing all-solid lithium batteries, the low ionic conductivity and unstable P-S bonds of sulfide solid electrolyte materials lead to a shortening of the battery cycle life and poor structural stability of the amorphous materials.

Method used

The solid electrolyte material of Li6+xPSe5+xI1-x is used to regulate the carrier concentration and ion diffusion channels in the unit cell through Se2-/I-inequal replacement, and a stable P-Se bond is used to replace the P-S bond to improve the crystallinity and electrochemical stability of the material.

Benefits of technology

High ionic conductivity (no less than 10-4S/cm) and low activation energy are achieved, which enhances electrochemical stability and interface compatibility and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118507816B_ABST
    Figure CN118507816B_ABST
Patent Text Reader

Abstract

The present invention provides a solid electrolyte material and a preparation method and application thereof, belonging to the technical field of lithium battery application. The solid electrolyte material has the following chemical formula Li 6+x PsE 5+ x I 1‑x , 0<x<1. By using Li6PSe5I and Li7PSe6 as the matrix, Se 2‑ / I ‑ Proportion obtained. 2‑ / I ‑ Non-equivalent substitution adjusts the carrier concentration and ion diffusion channel size in the unit cell, improving ion conductivity; changes the lattice softness and lattice vibration frequency, reducing the diffusion activation energy of ions; adjusts the bond energy, enhances the electrochemical stability of the material, reduces the degree of side reactions during the charge and discharge cycle, and enhances the electrode / electrolyte interface compatibility. The preparation method of this solid electrolyte material is simple, ensuring efficient ion transmission while ensuring good interface stability, which is conducive to solving practical problems such as the damage to the cycle life of the full battery caused by existing sulfide solid electrolytes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery application, and in particular relates to a solid electrolyte material and a preparation method and application thereof. Background Art

[0002] Compared with the shortcomings of organic electrolytes in traditional lithium-ion batteries that are easy to burn and explode, all-solid-state lithium metal batteries using solid electrolytes not only have higher safety performance, but also have higher energy density because they can be adapted to high-voltage positive electrodes and high-specific-capacity lithium negative electrodes. However, in the commercialization process, the ionic conductivity of solid electrolytes, as key components, and their compatibility and stability with electrodes have become bottlenecks for their further development. In theory, the ionic conductivity of a good solid electrolyte material should be at least 10 -4 S / cm, and ensure good electrode / electrolyte interface contact, low interface resistance, high electrochemical stability, and good interface kinetics.

[0003] The solid electrolyte with the highest ionic conductivity currently comes from Li 10 MP 2 S 12 (LMPS, M=Si, Ge, Sn), Li 6 PS 5 X (LPSX, X = Cl, Br, I) is the representative sulfur family. However, the ion-electron mixed conductive byproducts produced by the decomposition of LMPS materials during the cycle will continue to aggravate the occurrence of side reactions and seriously damage the cycle life of the battery. Therefore, in order to realize the commercialization of all-solid-state batteries faster, the research focus has turned to LPSX materials. In LPSX, when X = Cl and Br, it has a value greater than 10 -3 S / cm ionic conductivity, but still does not have the air stability and electrochemical stability required by the application due to the active PS bonds. In contrast, LiI produced by the decomposition of LPSI can serve as a passivation layer to alleviate the further occurrence of side reactions between the electrode / electrolyte, but the low ionic conductivity limits the application of LPSI in all-solid-state batteries. In order to solve the problem of low ionic conductivity of LPSI, some reports have increased the I by eliminating the annealing process. - / S 2- The disorder makes the glass-ceramic LPSI show 10 -3 S / cm level ionic conductivity, such as the microcrystalline glass argyrodite phase powder material Li mentioned in Chinese patent CN 113506911 B 6-x PS 5-x I 1+x, 0 < x ≤ 1. However, compared with the crystalline structure, the structural stability of amorphous materials is often poor, which will affect the long-cycle performance of the battery. How to maintain good cycle stability of all-solid-state batteries while ensuring high-speed ion diffusion is a technical problem that urgently needs to be solved. Summary of the Invention

[0004] The purpose of the present invention is to provide a solid electrolyte material, its preparation method and application in view of the above deficiencies of the prior art. The preparation method of this solid electrolyte material is simple, with high ionic conductivity, low activation energy, low interfacial impedance to lithium and high stability to lithium. Compared with amorphous LPSI-based solid electrolytes, the solid electrolyte material provided by the present invention has high crystallinity, ensuring structural stability. In addition, using more stable P-Se bonds instead of P-S bonds reduces the activity of harmful side reactions, and can further solve problems in practical applications such as the short cycle life of all-solid-state batteries caused by the low electrochemical stability of sulfide solid electrolytes.

[0005] To achieve the above purpose, the present invention adopts the following technical solutions:

[0006] The first object of the present invention is to provide a solid electrolyte material, and the solid electrolyte material has the following chemical formula Li 6+x PSe 5+x I 1-x , 0 < x < 1.

[0007] Further, the crystal of the solid electrolyte material is a cubic phase structure, belonging to F- 43 m space group.

[0008] Further, the lattice constant of the crystal is in the range of 10.559 Å to 10.429 Å.

[0009] Further, the lithium ion conductivity of the solid electrolyte material is not less than 10 -4 S / cm, and the activation energy is not higher than 0.4 eV.

[0010] Further, the increase in the ionic conductivity of the solid electrolyte material comes from changes in carrier concentration, ion diffusion channels, and lattice polarity, and the degree of anion disorder is always maintained at a low level (<10%).

[0011] The second object of the present invention is to provide a preparation method of the above solid electrolyte material, including the following specific steps:

[0012] Step S1, in an inert gas atmosphere, mix Li 2 Se, LiI, P, Se according to Li 6+x PSe 5+x X1-x The stoichiometric ratio is weighed, and the mixture is evenly mixed by ball milling to obtain a ball mill material;

[0013] Step S2, under an inert gas atmosphere, dry-pressing and granulating the ball mill material to obtain an intermediate, sintering the intermediate in a closed tube to obtain a solid product, and crushing the obtained solid product to obtain a solid electrolyte material.

[0014] Furthermore, in step S1, the ball milling process is performed using a planetary ball mill or a high-energy ball mill, the ball milling speed is 200 to 550 r / min, and the ball milling time is 0.5 to 20 h.

[0015] Furthermore, in step S2, the sintering process is to heat up to 550°C at a rate of 0.5°C / min, and keep the temperature at 550°C for 10 to 20 hours to perform a solid phase synthesis reaction. After the reaction is completed, the product together with the closed tube is moved into a ventilated place or water or liquid nitrogen to quickly cool down.

[0016] A third object of the present invention is to provide a solid electrolyte comprising the above-mentioned solid electrolyte material.

[0017] A fourth object of the present invention is to provide a solid electrolyte membrane comprising the above-mentioned solid electrolyte as a main component.

[0018] The fifth object of the present invention is to provide a lithium-ion battery, which is a lithium-ion battery having a positive electrode including a positive electrode active material layer, an electrolyte layer and a negative electrode including a negative electrode active material layer, and at least one of the positive electrode active material layer, the electrolyte layer and the negative electrode active material layer contains the above-mentioned solid electrolyte material.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention uses Li 6 PsE 5 I. Li 7 PsE 6 As the matrix, through Se 2- / I - Unequal substitution adjusts the carrier concentration and ion diffusion channel size in the unit cell, thereby improving the ionic conductivity, reducing the interaction between anions and cations, and improving the ionic conductivity of the electrolyte material.

[0021] (2) The present invention adjusts Se 2- / I - The ratio changes the lattice softness, lattice vibration frequency, and interaction force between anions and cations, thereby reducing the diffusion activation energy of ions.

[0022] (3) The present invention introduces a higher content of Se, which not only replaces the unstable PS bond in the conventional sulfur-based solid electrolyte with a stable P-Se bond, but also adjusts the Se 2- / I - The ratio further adjusts the energy of the system, thereby enhancing the electrochemical stability of the material, reducing the degree of side reactions during the charge and discharge cycle, and enhancing the compatibility of the electrode / electrolyte interface. While ensuring efficient ion transmission, it also ensures good interface stability, which is conducive to solving practical problems in existing all-solid-state lithium battery technology, such as the sulfide solid electrolyte damaging the cycle life of the entire battery.

[0023] (4) The process of the present invention is simple and efficient, the preparation process is simple, and it is suitable for commercial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The XRD diffraction patterns of Examples 1-3 and Comparative Examples 1 and 2 are shown;

[0025] Figure 2 For Examples 1-3 and Comparative Examples 1 and 2 31 P MAS NMR spectrum;

[0026] Figure 3 The AC impedance spectra of Examples 1-4 and Comparative Examples 1 and 2 at room temperature;

[0027] Figure 4 Arrhenius curves of Examples 1-4 and Comparative Examples 1 and 2 at different temperatures;

[0028] Figure 5 The rotation coordinate system of Examples 1-3 and Comparative Example 1 is 31 P NMR spin-lattice relaxation time ( T 1ρ )picture;

[0029] Figure 6 The lithium metal symmetric battery was assembled as the solid electrolyte in Example 2 of the present invention, and the current was 0.05-0.1 mA / cm 2 The charge and discharge diagram below. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the present invention clearer, embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0031] Example 1

[0032] The present invention provides a solid electrolyte material Li 6.8 PsE 5.8 I 0.2 Preparation method.

[0033] The specific steps are as follows:

[0034] Step S1, under an inert gas atmosphere, according to Li 2 The stoichiometric ratio of Se: LiI: P: Se = 3.3: 0.2: 1: 3 was weighed, and the powder was put into a ball mill at a ball-to-material ratio of 40:1, and ball milled at a speed of 550 r / min for 20 h to obtain ball mill material;

[0035] Step S2, in an inert gas atmosphere, put the ball mill into a mold and dry press it into a sheet material with a thickness of about 1 mm under a pressure of 3t, granulate it after demolding, and encapsulate it in a vacuum quartz tube. Put the quartz tube into a muffle furnace, heat it to 550°C at a rate of 0.5°C / min, and keep it at 550°C for 10 h to perform a solid phase synthesis reaction. After the reaction is completed, move the product together with the closed tube into a ventilated place or water or liquid nitrogen to quickly cool it down. Grind the obtained solid product to obtain the Se-doped LPSX solid electrolyte material Li 6.8 PsE 5.8 I 0.2 Steps S1-S2 are all performed in a glove box protected by inert gas.

[0036] Example 2

[0037] The present invention provides a solid electrolyte material Li 6.5 PsE 5.5 I 0.5 Preparation method.

[0038] The specific steps are as follows:

[0039] Step S1, under an inert gas atmosphere, according to Li 2 The stoichiometric ratio of Se: LiI: P: Se = 3: 0.5: 1: 3 was weighed, and the powder was put into a ball mill at a ball-to-material ratio of 40:1, and ball milled at a speed of 550 r / min for 20 h to obtain ball mill material;

[0040] Step S2, in an inert gas atmosphere, put the ball mill into a mold and dry press it into a sheet material with a thickness of about 1 mm under a pressure of 3t, granulate it after demolding, and encapsulate it in a vacuum quartz tube. Put the quartz tube into a muffle furnace, heat it to 550°C at a rate of 0.5°C / min, and keep it at 550°C for 10 h to perform a solid phase synthesis reaction. After the reaction is completed, move the product together with the closed tube into a ventilated place or water or liquid nitrogen to quickly cool it down. Grind the obtained solid product to obtain the Se-doped LPSX solid electrolyte material Li 6.5 PsE 5.5 I 0.5 Steps S1-S2 are all performed in a glove box protected by inert gas.

[0041] Example 3

[0042] The present invention provides a solid electrolyte material Li 6.2 PsE 5.2 I 0.8 Preparation method.

[0043] The specific steps are as follows:

[0044] Step S1, under an inert gas atmosphere, according to Li 2 The stoichiometric ratio of Se: LiI: P: Se = 2.7: 0.8: 1: 3 was weighed, and the powder was put into a ball mill at a ball-to-material ratio of 40:1, and ball milled at a speed of 550 r / min for 20 h to obtain ball mill material;

[0045] Step S2, in an inert gas atmosphere, put the ball mill into a mold and dry press it into a sheet material with a thickness of about 1 mm under a pressure of 3t, granulate it after demolding, and encapsulate it in a vacuum quartz tube. Put the quartz tube into a muffle furnace, heat it to 550°C at a rate of 0.5°C / min, and keep it at 550°C for 10 h to perform a solid phase synthesis reaction. After the reaction is completed, move the product together with the closed tube into a ventilated place or water or liquid nitrogen to quickly cool it down. Grind the obtained solid product to obtain the Se-doped LPSX solid electrolyte material Li 6.2 PsE 5.2 I 0.8 Steps S1-S2 are all performed in a glove box protected by inert gas.

[0046] Example 4

[0047] The present invention provides a solid electrolyte material Li 5.5 PsE 4.5 I 1.5 Preparation method.

[0048] The specific steps are as follows:

[0049] Step S1, under an inert gas atmosphere, according to Li 2 The stoichiometric ratio of Se: LiI: P: Se = 2: 1.5: 1: 2.5 was weighed, and the powder was put into a ball mill at a ball-to-material ratio of 40:1, and ball milled at a speed of 550 r / min for 20 h to obtain ball mill material;

[0050] Step S2, in an inert gas atmosphere, put the ball mill into a mold and dry press it into a sheet material with a thickness of about 1 mm under a pressure of 3t, granulate it after demolding, and encapsulate it in a vacuum quartz tube. Put the quartz tube into a muffle furnace, heat it to 550°C at a rate of 0.5°C / min, and keep it at 550°C for 10 h to perform a solid phase synthesis reaction. After the reaction is completed, move the product together with the closed tube into a ventilated place or water or liquid nitrogen to quickly cool it down. Grind the obtained solid product to obtain the Se-doped LPSX solid electrolyte material Li 5.5 PsE 4.5 I 1.5 Steps S1-S2 are all performed in a glove box protected by inert gas.

[0051] Comparative Example 1

[0052] Comparative Example 1 is a type of low ionic conductivity sulfide solid electrolyte material Li 7 PsE 6 The preparation method thereof is:

[0053] Step S1, under an inert gas atmosphere, according to Li 2 The stoichiometric ratio of Se: P: Se = 3.5: 1: 2.5 was weighed, and the powder was put into a ball mill at a ball-to-material ratio of 40:1, and ball milled at a speed of 550 r / min for 20 h to obtain ball mill material;

[0054] Step S2, in an inert gas atmosphere, put the ball mill into a mold and dry press it under a pressure of 3t into a sheet material with a thickness of about 1mm, granulate it after demoulding, and encapsulate it in a vacuum quartz tube. Put the quartz tube into a muffle furnace, heat it to 550℃ at a rate of 0.5℃ / min, and keep it at 550℃ for 10 hours to carry out solid phase synthesis reaction. After the reaction is completed, move the product together with the closed tube into a ventilated place or water or liquid nitrogen to quickly cool it down. Grind the obtained solid product to obtain the comparative example material Li 6 PS 5 I. Steps S1-S2 are all performed in a glove box protected by inert gas.

[0055] Comparative Example 2

[0056] Comparative Example 1 is a type of low ionic conductivity sulfide solid electrolyte material Li 6 PsE5 1. Its preparation method is:

[0057] Step S1, under an inert gas atmosphere, according to Li 2 The stoichiometric ratio of Se: LiI: P: Se = 2.5: 1: 1: 2.5 was weighed, and the powder was put into a ball mill at a ball-to-material ratio of 40:1, and ball milled at a speed of 550 r / min for 20 h to obtain ball mill material;

[0058] Step S2, in an inert gas atmosphere, put the ball mill into a mold and dry press it under a pressure of 3t into a sheet material with a thickness of about 1mm, granulate it after demoulding, and encapsulate it in a vacuum quartz tube. Put the quartz tube into a muffle furnace, heat it to 550℃ at a rate of 0.5℃ / min, and keep it at 550℃ for 10 hours to carry out solid phase synthesis reaction. After the reaction is completed, move the product together with the closed tube into a ventilated place or water or liquid nitrogen to quickly cool it down. Grind the obtained solid product to obtain the comparative example material Li 6 PsE 5 I. Steps S1-S2 are all performed in a glove box protected by inert gas.

[0059] In order to better illustrate the electrochemical properties of the solid electrolyte material prepared by the present invention, the applicant conducted the following research:

[0060] Performance characterization:

[0061] refer to Figure 1 , which is the XRD comparison diagram of Examples 1-3 and Comparative Examples 1 and 2. It can be seen from the figure that the synthesized solid electrolyte material has high purity. There are differences in the diffraction peak angles between Examples 1-3 and Comparative Examples 1 and 2, which represents the change in the unit cell size caused by element doping. The lattice constants (a=b=c) of Examples 1-3 are 10.4299 Å, 10.5022 Å, 10.5371 Å, and 10.5261 Å, respectively, and the lattice constants (a=b=c) of Comparative Examples 1 and 2 are 10.4751Å and 10.5589Å, respectively. The increase in ionic conductivity comes from changes in carrier concentration, ion diffusion channels, and lattice polarity, and the anion disorder is always maintained at a low level (<10%).

[0062] refer to Figure 2 , which is the result of the experiments of Examples 1-3 and Comparative Examples 1 and 2 at a magic angle spinning speed of 22 kHz 31 P MAS NMR experiment, from the chemical shift, it can be seen that the structure is the target phase and has high purity. 2- The weaker electronegativity makes 31 The shielding effect of P is enhanced, and the difference in the peak line shape indicates the difference in the microscopic local structure in the unit cell.

[0063] refer to Figure 3 , are the AC impedance spectra of Examples 1-4 and Comparative Examples 1 and 2 at room temperature. It can be seen from the figure that the resistance of Examples 1-4 at room temperature is significantly lower than that of Comparative Example 1, indicating that Se 2- / I - The adjustment of the ratio has a positive effect on the improvement of ion transmission performance.

[0064] refer to Figure 4 , are the Arrhenius curves of Examples 1-4 and Comparative Examples 1 and 2 at different temperatures. The activation energy of ion diffusion can be obtained by the slope. It can be seen from the figure that the activation energy of Examples 1-4 is significantly lower than that of Comparative Example 1.

[0065] refer to Figure 5 , is the rotation coordinate system of Examples 1-3 and Comparative Example 1 31 P NMR spin-lattice relaxation time ( T 1ρ ). 31 P and 7 Li has a similar resonance frequency, and its relaxation process is determined by the surrounding Li + The fluctuation of motion is caused by the detection of Li + Good probe of kinetic behavior. At room temperature, 31 P T 1ρ Size and Li involved in inter-cage diffusion per unit time + As can be seen from the figure, when 0≤x≤0.5, the total amount of Li+ participating in inter-cage diffusion per unit time continues to increase, but when x>0.5, inter-cage diffusion begins to be inhibited by the reduction of diffusion channels and the slowing of lattice vibration.

[0066] The solid electrolyte materials prepared in Examples 1-4 and Comparative Example 1 were tested for performance:

[0067] (1) Conductivity test

[0068] In a glove box, a powder forming mold made of stainless steel and with an insulating layer on the top and bottom was used to apply a pressure of 360 MPa to Examples 1-4 and Comparative Example 1, respectively, to press into sheets with a diameter of 10 mm. An electrochemical workstation was used to perform an AC impedance test at different temperatures to obtain ionic conductivity, and the activation energy was calculated based on the relationship between conductivity and temperature; an electrochemical workstation was used to perform a polarization test to obtain electronic conductivity.

[0069] Test results:

[0070] Compared with Comparative Examples 1 and 2, adjusting Se 2- / I -After the comparison, the ionic conductivity of Examples 1-3 increased significantly, and the activation energy decreased significantly, among which Example 2 had the best performance. The ionic conductivity of Example 4 was slightly lower than that of Comparative Example 2, but it reduced the cost while ensuring good conductivity, which is conducive to commercial promotion. The specific results are shown in Table 1:

[0071] Table 1.

[0072]

[0073] (2) Lithium metal stability test

[0074] The lithium metal symmetric battery was assembled using Example 2 as the solid electrolyte, and was labeled as Li / Li 6.5 PsE 5.5 I 0.5 / Li. At room temperature, 0.05~0.1 mA / cm 2 Long-term cycle stability test was carried out at different current densities.

[0075] Test results:

[0076] Symmetrical battery Li / Li 6.5 PsE 5.5 I 0.5 / Li at room temperature 0.05~0.1 mA / cm 2 The charge and discharge cycle diagram is as follows Figure 6 As shown, the battery is at 0.05 mA / cm 2 After cycling for 1000 hours at a current density of 0.1 mA / cm 2 The cycle continued for more than 2000 hours at the current density, showing good cycle stability, indicating that Example 2 has low lithium interface impedance and high electrochemical stability, which is beneficial to improving the cycle stability performance of the all-solid-state battery.

[0077] For matters not mentioned above, the prior art applies.

[0078] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A solid electrolyte material, characterized in that: The solid electrolyte material has the following chemical formula Li 6+x PsE 5+ x I 1-x , 0<x≤0.8, the crystal of the solid electrolyte material is a cubic phase structure, belonging to F-43m Space group.

2. The solid electrolyte material according to claim 1, characterized in that At room temperature, the lithium ion conductivity is 1.1×10 -3 ~3.5×10 -3 S / cm, and the activation energy is less than 0.4 eV.

3. The solid electrolyte material according to claim 2, characterized in that The lattice constants of the crystals are in the range of 10.559 Å to 10.429 Å.

4. A method for preparing a solid electrolyte material according to any one of claims 1 to 3, characterized in that: The specific steps include: S1. In an inert gas atmosphere, Li2Se, LiI, P, Se were mixed according to Li 6+x PsE 5+x I 1-x The stoichiometric ratio is weighed, and the mixture is evenly mixed by ball milling to obtain a ball mill material; S2. In an inert gas atmosphere, dry-pressing and granulating the ball mill material to obtain an intermediate, sintering the intermediate in a closed tube to obtain a solid product, and crushing the obtained solid product to obtain a solid electrolyte material.

5. The preparation method according to claim 4, characterized in that: In step S1, the ball milling process is performed using a planetary ball mill or a high-energy ball mill.

6. The preparation method according to claim 5, characterized in that The powder was put into a ball mill at a ball-to-material ratio of 40:1, and ball milled at a speed of 550 r / min for 20 h to obtain ball mill material.

7. The preparation method according to claim 4, characterized in that: In step S2, the sintering process is to heat up to 550°C at a rate of 0.5°C / min, keep the temperature at 550°C for 10 to 20 hours to perform a solid phase synthesis reaction, and after the reaction is completed, move the product together with the closed tube into a ventilated place or water or liquid nitrogen to quickly cool down.

8. A solid electrolyte, characterized in that The method comprises the solid electrolyte material according to any one of claims 1 to 3.

9. A solid electrolyte membrane, characterized in that: Contains the solid electrolyte material according to claim 1 as a main component.

10. A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, characterized in that: At least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer includes the solid electrolyte material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • A sulfide solid electrolyte material and its preparation method and application, all-solid-state lithium battery

    CN113506911B

  • Preparation and application of group IIA element and double halogen doped sulfide solid electrolyte

    CN114649562A

  • Solid electrode including electrolyte-impregnated active material particles

    US20170162862A1